Interactive Multimedia "Porogapit Math" Based on Bar Diagrams in Mathematics Content on Structured Division for Elementary School Students - Ni Komang Ayu Trisna Sancita Dewi; I Wayan Wiarta (Jurnal Edutech Undiksha, 2025)
Learning media plays a very important role in teaching Mathematics at the elementary school level because it helps students transform abstract concepts into more concrete and understandable forms. However, the low understanding of Grade III students regarding long division material is caused by the limited availability of engaging and contextual learning media. This study aims to analyze the effectiveness of the interactive multimedia “Porogapit Math” based on bar diagrams, which is feasible and effective for use in Mathematics learning. The development model employed in this study was the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 28 Grade III students. Data collection methods and instruments included questionnaires to test the validity and practicality of the multimedia, as well as essay tests to measure its effectiveness. Data analysis techniques were conducted using quantitative descriptive, qualitative, and inferential methods. Based on the results of the t-test, the obtained t-value was 2.287, while the t-table value with df = (n – 1) = 27 at a 5% significance level was 2.052, indicating that tvalue > ttable, meaning that H₀ was rejected. Therefore, it can be concluded that the interactive multimedia “Porogapit Math” based on bar diagrams is effective for teaching division material in Grade III. The implication of this study is that “Porogapit Math” can serve as an innovative learning alternative that facilitates students’ understanding of long division concepts in a visual, interactive, and enjoyable way.